Development of a speed warning device for micro-mobility devices - Gan, Zhi Yuan (Nanyang Technological University, 2020)
The rise of Personal Mobility Devices (PMD) usage has increased the convenience of many commuters in Singapore. Unfortunately, as PMD users tend to ride their devices on the pavements, it has caused a string of injuries due to collisions with pedestrians. To reduce such incidents, the government has banned the use of PMDs on pavements since November 2019. The development of a speed warning device for micro-mobility devices has been proposed by Dr. F.F. Yap. It would be designed to warn a PMD user of an imminent collision with a pedestrian, providing ample time for the rider to make the necessary speed adjustments or stop. This report will discuss development of the proposed prototype, its electrical circuit, and software codes, at various stages. The test results of the prototype are also presented and analysed for its effectiveness. Lastly, future improvements to the product will be discussed. The test results obtained showed that the present Speed Warning Device prototype can work under the bright light condition. It has obtained an effectiveness of 72% for a stationary pedestrian and 65% for a pedestrian in constant movement. It is hoped that the development of this device will increase the safety of PMD riding, and that Singapore will feel comfortable in allowing PMDs back onto pavement